Automated high resolution optical mapping using arrayed, fluid-fixed DNA molecules - Jing, Junping (The National Academy of Sciences, 1998)
New mapping approaches construct ordered restriction maps from fluorescence microscope images of individual, endonuclease-digested DNA molecules. In optical mapping, molecules are elongated and fixed onto derivatized glass surfaces, preserving biochemical accessibility and fragment order after enzymatic digestion. Measurements of relative fluorescence intensity and apparent length determine the sizes of restriction fragments, enabling ordered map construction without electrophoretic analysis. The optical mapping system reported here is based on our physical characterization of an effect using fluid flows developed within tiny, evaporating droplets to elongate and fix DNA molecules onto derivatized surfaces. Such evaporation-driven molecular fixation produces well elongated molecules accessible to restriction endonucleases, and notably, DNA polymerase I. We then developed the robotic means to grid DNA spots in well defined arrays that are digested and analyzed in parallel. To effectively harness this effect for high-throughput genome mapping, we developed: (i) machine vision and automatic image acquisition techniques to work with fixed, digested molecules within gridded samples, and (ii) Bayesian inference approaches that are used to analyze machine vision data, automatically producing high-resolution restriction maps from images of individual DNA molecules. The aggregate significance of this work is the development of an integrated system for mapping small insert clones allowing biochemical data obtained from engineered ensembles of individual molecules to be automatically accumulated and analyzed for map construction. These approaches are sufficiently general for varied biochemical analyses of individual molecules using statistically meaningful population sizes.